Characterization and Manipulation of the Crosstalk Between Dendritic and Natural Killer Cells Within the Tumor Microenvironment - Jacobs, Benedikt; Gebel, Veronika; Heger, Lukas; Grèze, Victoria; Schild, Hansjörg; Dudziak, Diana; Ullrich, Evelyn (Frontiers in Immunology, 2021)
Cellular therapy has entered daily clinical life with the approval of CAR T cell therapeutics and dendritic cell (DCs) vaccines in the US and the EU. In addition, numerous other adoptive cellular products, including natural killer (NK) cells, are currently being evaluated in early phase I/ II clinical trials. Despite these promising successes, major obstacles make the path to therapeutic success difficult and pose challenges for science. These also include the strategies by which tumor cells escape the immune system, including the establishment of an immunosuppressive tumor microenvironment (TME). As part of the innate immune system DCs and NK cells are both present within the TME of various tumor entities. While NK cells are well known for their intrinsic anti-tumor activity by their cytotoxicity and the secretion of pro-inflammatory cytokines, the role of DCs within the TME is a double-edged sword since different DC subsets have been described with either tumor-promoting or -inhibiting characteristics. In this review, we will discuss recent findings on the interaction of DCs and NK cells under physiological conditions and within the TME. One focus is the crosstalk of various DC subsets with NK cells and their impact on the progression or inhibition of tumor growth. In addition, we will provide suggestions to overcome the immunosuppressive outcome of the DCs and NK cells interaction within the TME.